2017
DOI: 10.18805/lr.v0i0.7025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought stress on physiological and biochemicalchanges in Phaseolus vulgaris L.

Abstract: The present study investigated different levels (S1: 100% of field capacity-Control S2: 50% of field capacity-moderate stress; S3: 0% of field capacity-severe stress) of drought stress on oxidative damages and variations in antioxidants in the two bean varieties Bn-16 (drought-sensitive), to elucidate the antioxidative protective mechanism governing differential drought tolerance. The shoot fresh weight, shoot height, leaf number and area, RWC were reduced with different level of drought stress. However this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 21 publications
7
24
0
Order By: Relevance
“…Consequently, one of the parameters that helped us to identify the degree of susceptibility to oxidative stress damage in bush bean cultivars was the determination of the MDA content, especially at the vegetative stage. It has been shown that the increase in the MDA concentration in Phaseolus vulgaris plants is related to traits of susceptibility to water deficit conditions as a result of the increased production of oxygen free radicals that generate oxidative stress in cells (Kusvuran and Dasgan, 2017). In this sense, our results suggest that cultivars Cerinza and Bacat a showed the highest levels of damage by lipid peroxidation of cell membranes under water deficit conditions at the vegetative stage ( Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Consequently, one of the parameters that helped us to identify the degree of susceptibility to oxidative stress damage in bush bean cultivars was the determination of the MDA content, especially at the vegetative stage. It has been shown that the increase in the MDA concentration in Phaseolus vulgaris plants is related to traits of susceptibility to water deficit conditions as a result of the increased production of oxygen free radicals that generate oxidative stress in cells (Kusvuran and Dasgan, 2017). In this sense, our results suggest that cultivars Cerinza and Bacat a showed the highest levels of damage by lipid peroxidation of cell membranes under water deficit conditions at the vegetative stage ( Fig.…”
Section: Discussionsupporting
confidence: 54%
“…The obtained results showed that water deficit caused a reduction of the chlorophyll content in susceptible genotypes such as Bacata, whereas cultivar Bachue showed an increase in this variable. Reductions in the chlorophyll content have been reported in susceptible Phaseolus vulgaris L. genotypes to drought stress [35]. A reduction of chlorophyll under drought stress conditions is due to an overproduction of reactive oxygen species in the thylakoids [36].…”
Section: Discussionmentioning
confidence: 99%
“…The chlorophyll content was higher in leaves with broader and dark green (E-25YG-Cu and E-50M50LB-Cu) leaves than the landraces with narrower leaves. This reflects that chlorophyll content increases with leaf growth and development but decreases at the senescence stage (Pereyra et al 2014) and under stress conditions such as drought (Kusvuran and Dasgan 2017).…”
Section: Variation In Morpho-agronomic Traitsmentioning
confidence: 99%